Correlation of Body Mass Index and Waist Hip Ratio with lipid and hormone profile in women in menopausal transition (Journal of Health Sciences, 2014)
Introduction: Menopausal transition is a period characterised by psychic, somatic changes as well as changes in reproductive capabilities of a woman. It occurs as a consequence of ovarian’s function termination, and pertains to the periods of different meanings: perimenopause, menopause and postmenopause. Although there are numerous assessments of behaviour of the lipids and lipoproteins during menopausal transition, their relation to sexual hormones and body mass is still being assessed. The aim of this study is to determine the differences and connections between body mass index (BMI) and waist-hip ratio (WHR) and lipid and hormone profile among the assessees in premenopause, perimenopause and postmenopause.Methods: The assessment was done on 150 assessees divided in three groups of 50, such as: premenopause, perimenopause and postmenopause. The assessment included the following: interview, determination of BMI, WHR, and taking of blood sample and processing of hormone, lipid and lipoprotein concentration.Results: Based on the obtained results, it may not be concluded that BMI has a positive correlation with cholesterol and VLDL concentration in postmenopause, positive correlation with apo A in perimenopause and postmenopause, and positive correlation with Lp (a) and apo B in premenopause and perimenopause, while negative correlation with HDL and estradiol concentrations in premenopause.Conclusion: WHR has negative correlation with HDL concentration in premenopause and perimenopause, and a negative correlation with estradiol concentrations in premenopause.